1989
DOI: 10.1128/aem.55.3.711-716.1989
|View full text |Cite
|
Sign up to set email alerts
|

Initial Steps in the Degradation of Phosphinothricin (Glufosinate) by Soil Bacteria

Abstract: Three hundred bacterial isolates from soil were tested for resistance against phosphinothricin [PPT; DL-homoalanin-4-yl(methyl)phosphinic acid], the active ingredient of the herbicide BASTA. Eight resistant bacterial strains and Escherichia coli were analyzed for PPT-transforming activities. At least three different enzymatic reactions could be detected in cell extracts. In six strains an acetyltransferase was active, synthesizing N-acetyl-PPT in the presence of PPT and acetyl coenzyme A. All strains could deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 22 publications
3
44
1
Order By: Relevance
“…Changes in one of these molecular regions will decrease the utilization capacity of Pseudomonas towards these phosphonates as source for phosphorus. This hypothesis is confirmed by the reports of TEBBE and REBER (1988) and BARTSCH and TEBBE (1989) who demonstrated that phosphinothricin is metabolized by soil bacteria but may not be utilized as source of phosphorus. But in order to get a clear understanding of the enzymological cleavage of C-P-bond in Pseudomonas the metabolism of phosphonates must be investigated with purified enzymes.…”
Section: Discussionsupporting
confidence: 69%
“…Changes in one of these molecular regions will decrease the utilization capacity of Pseudomonas towards these phosphonates as source for phosphorus. This hypothesis is confirmed by the reports of TEBBE and REBER (1988) and BARTSCH and TEBBE (1989) who demonstrated that phosphinothricin is metabolized by soil bacteria but may not be utilized as source of phosphorus. But in order to get a clear understanding of the enzymological cleavage of C-P-bond in Pseudomonas the metabolism of phosphonates must be investigated with purified enzymes.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, one offset to the problem of enhanced biodegradation of soilapplied pesticides has been the discovery of many novel gene/enzyme systems responsible for degrading the various chemistries among the soil microflora. Some of these gene/enzyme systems have subsequently proven extremely useful in the development of transgenic herbicide-resistant crops (Bartsch and Tebbe 1989;Wehrmann et al 1996;Castle et al 2004). Others have been used in the development of bioremediation agents for the clean-up of contaminated environments (Sutherland et al 2004;Scott et al 2008;Russell et al 2011).…”
Section: Evolutionary Issues In Emergent Weedsmentioning
confidence: 99%
“…It is phytotoxic by interfering with photophosphorylation through accumulation of intracellular NH þ 4 [3,4] but its toxicity to mammals is rather low [5,6]. Some microbial activities, including growth of several soil bacteria [7] and of Esche-richia coli [8] or the nodulation of Lucerne (alfalfa) roots by Sinorhizobium meliloti [9] are sensitive to concentrations of 1 mM or less under laboratory conditions. In contrast, it has been reported that many bacteria in surface or subsurface soil are resistant to glufosinate [7,8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Some microbial activities, including growth of several soil bacteria [7] and of Esche-richia coli [8] or the nodulation of Lucerne (alfalfa) roots by Sinorhizobium meliloti [9] are sensitive to concentrations of 1 mM or less under laboratory conditions. In contrast, it has been reported that many bacteria in surface or subsurface soil are resistant to glufosinate [7,8,10,11]. In soil, glufosinate is quickly degraded by deamination and decarboxylation to a non-toxic intermediate, which is further mineralised [12^15].…”
Section: Introductionmentioning
confidence: 99%